Transformações na paisagem de Sabará: uma investigação das diferentes historicidades e das construções identitárias - Jaqueline Duarte Santos (2013)
The current investigation analyses the modifications in the formal, physical and urban character of the sociospatial cutting that was established, which includes some districts that are situated close to the traditional colonial context of Sabará. Simultaneously, a social analysis was developed, aimming at the understanding about the valour and identity constructions that characterize that local comunities. The discussion arise from the idea of the plasticity of the cultures as much as of the identities, that is fomented, more and more, by the crescent hybridation processes of the modernity. Thus, the inquiry about the behavior of these cultural dialectics increases: at times allow themselves to get hybrid, through the incorporation of another symbolic and identity references; sometimes construct and keep its own constructions of valour. So, for achieving the aims and the results of this investigation was picked out a diversified landscape of Sabará, that juxtaposes to the traditional colonial remaining the new landscapes, which ones present industrial, progressist, contemporaneous influences, among others. The interdisciplinary character is one essential instrument for the research, due to the intention of apprehending the way the preexistent built enviromnment the colonial cultural, urban and architectonic heritage of the city -, influences the identity construction even in that new areas, in which the hybrid multicultural characters are manifested in the urban, architectonic and sociocultural meaning. So, the theories must be plural and embracing the concepts and ideas of disciplines as architecture and urbanism, as well as sociology and anthropology. In this manner, it is intended to investigate, at a singular and under transformation context, in which the dialectic between traditional spaces and modernity contexts as presented in the established sociospatial cutting for analysis in Sabará , the identity tenuous equilibrium, this one that is challenged when faced to the alterity and difference.